Una experiencia audiovisual con mucha post - Castillo Sánchez, Lucía Paola (2023)
In the following report, I will be narrating the most important aspects of my professional life since graduating the university. With nearly 20 years of experience in the field of audiovisual communication, creating corporate videos and specializing in video editing, post-production, and 2D animation, I have worked in both the public and private sectors, always focused on creating audiovisual content. My objective has been to support the clients' vision, always striving to exceed expectations. In this paper, I will describe my experience in an educational project that started out as quite ambitious and which I consider encompasses various aspects of communication.